2005
DOI: 10.1074/jbc.m407179200
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein/Kinin Protects against Myocardial Apoptosis after Ischemia/Reperfusion via Akt-Glycogen Synthase Kinase-3 and Akt-Bad·14-3-3 Signaling Pathways

Abstract: Our previous study has shown that human tissue kallikrein protected against ischemia/reperfusion-induced myocardial injury. In the present study, we investigated the protective role of local kallikrein gene delivery in ischemia/reperfusion-induced cardiomyocyte apoptosis and its signaling mechanisms in promoting cardiomyocyte survival. Adenovirus carrying the human tissue kallikrein gene was delivered locally into the heart using a catheter-based technique. Expression and localization of recombinant human kall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 38 publications
5
87
0
1
Order By: Relevance
“…Our previous study showed that local injection of adenovirus carrying the human tissue kallikrein into the heart protects against cardiomyocyte apoptosis after acute myocardial ischemia/reperfusion [19]. However, kallikrein protein infusion has advantages over adenovirus-mediated delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that local injection of adenovirus carrying the human tissue kallikrein into the heart protects against cardiomyocyte apoptosis after acute myocardial ischemia/reperfusion [19]. However, kallikrein protein infusion has advantages over adenovirus-mediated delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice expressing wild-type GSK-3β in the heart exhibit dramatic impairment of normal post-natal cardiomyocyte growth as well as abnormal cardiac contractile function [16]. The protective effects of Kallikrein/kinin in ischemia/reperfusion-induced apoptosis are suggested to involve Akt-mediated inactivation of GSK-3β [17]. Inhibition of GSK-3β is also shown to inhibit hypoxia/reperfusion-induced cardiac myocyte apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of angiotensin-converting enzyme inhibition in hypertension, cardiovascular and renal disease can be partially attributed to kinin accumulation resulting from the activation of the B2 receptor [16,17] . Previous animal studies suggested that kallikrein/kinin protects against myocardial apoptosis after ischemia/reperfusion injury [18,19] . In our study, delivery of the kallikrein gene protected against cardiomyocyte apoptosis in SHRs; therefore, this gene could potentially be used to treat hypertension.…”
Section: Discussionmentioning
confidence: 99%